Biotinylation of optically responsive gold/polyelectrolyte nanostructures - Pereira, Sonia O.
The development of analytical platforms incorporating Au nanoparticles (NPs) for optical biosensing requires approaches to produce optically responsive and target selective materials. In the present work, fluorescence emission and bioselectivity of Au NPs have been combined by a one-step surface functionalization using fluorescein isothiocyanate (FITC) and biotin. First, colloidal Au NPs (d= 17.7 +/- 2.7 nm) exhibiting an absorption maximum (lambda(max)) at 524.5 nm have been surface-modified with the polyelectrolytes (PE) poly(allylamine hydrochloride) (PAH) and poly(sodium styrene sulfonate) (PSS). Two strategies were then assessed for the functionalization of Au NPs: (i) functionalization of PAH with biotin and subsequent coating of the NPs and (ii) surface modification of the NPs with the PE followed by post-functionalization with biotin. The effect of the surface functionalization on the colloidal NPs was monitored by optical absorption and fluorescence emission spectroscopies, dynamic light scattering (DLS), zeta potential measurements and transmission electron microscopy (TEM). Finally, the optical response and specificity of the functionalized NPs towards avidin was evaluated by optical measurements. The results have shown that these hybrid nanostructures have potential to be used in biosensing. In particular, the aggregation of biotinylated Au assemblies associated with the biorecognition of avidin could be assessed by fluorescence emission spectroscopy.